Development of Learning Media Using Canva Application in Grade VII Informatics Subject on Computational Thinking Material with the ADDIE Model - Hidayat, Muhammad Nur; Muslimin, Ikhwannul; Purnamasari, Ramdhani (FKIP - Universitas Riau, 2025)
This study aims to develop Canva-based learning media for Grade VII Informatics subjects at SMP Negeri 5 Palibelo using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The background of this research is the low effectiveness of conventional media such as textbooks and Power Point, which make students passive and less motivated. The development process included needs analysis through observation and teacher interviews, interactive media design, product development, classroom implementation, and formative evaluation. Media expert validation obtained feasibility percentages of 88.57% and 94.67% (very feasible), while material experts gave 84% and 82% (very feasible). A trial involving 21 students resulted in positive responses with an average of 89.25% (very feasible). These findings indicate that Canva-based learning media is effective, engaging, and capable of improving student motivation and involvement. Therefore, Canva can be used as an innovative alternative for Informatics learning media development that is aligned with the demands of the digital era.